Assessing the use of blood microRNA expression patterns for predictive diagnosis of myxomatous mitral valve disease in dogs - Palarea-Albaladejo, Javier; Bode, Elizabeth F.; Partington, Catheryn; Basili, Mattia; Mederska, Elzbieta; Hodgkiss-Geere, Hannah; Capewell, Paul; Chauché, Caroline; Coultous, Robert M.; Hanks, Eve; Dukes-McEwan, Joanna (Frontiers in Veterinary Science, 2024)
BackgroundMyxomatous mitral valve disease (MMVD) is a common, acquired, and progressive canine heart disease. The presence of heart murmur and current cardiac biomarkers are useful in MMVD cases but are not sufficiently discriminatory for staging an individual patient.ObjectivesThis study aimed to conduct a preliminary assessment of canine serum and plasma expression profiles of 15 selected miRNA markers for accurate discrimination between MMVD patients and healthy controls. Additionally, we aim to evaluate the effectiveness of this method in differentiating between pre-clinical (stage B1/B2) and clinical (stage C/D) MMVD patients.AnimalsClient-owned dogs (n = 123) were recruited for the study. Following sample exclusions (n = 26), healthy controls (n = 50) and MMVD cases (n = 47) were analyzed.MethodsA multicenter, cross-sectional, prospective investigation was conducted. MicroRNA expression profiles were compared among dogs, and these profiles were used as input for predictive modeling. This approach aimed to distinguish between healthy controls and MMVD patients, as well as to achieve a more fine-grained differentiation between pre-clinical and clinical MMVD patients.ResultsPerformance metrics revealed a compelling ability of the method to differentiate healthy controls from dogs with MMVD (sensitivity 0.85; specificity 0.82; and accuracy 0.83). For the discrimination between the pre-clinical (n = 29) and clinical (n = 18) MMVD cases, the results were promising (sensitivity 0.61; specificity 0.79; and accuracy 0.73).Conclusion and clinical importanceThe use of miRNA expression profiles in combination with customized probabilistic predictive modeling shows good scope to devise a reliable diagnostic tool to distinguish healthy controls from MMVD cases (stages B1 to D). Investigation into the ability to discriminate between the pre-clinical and clinical MMVD cases using the same method yielded promising early results, which could be further enhanced with data from an increased study population.